HUBUNGAN EFIKASI DIRI DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI KLINIK PRATAMA ISLAM MEDINA KARAWANG TAHUN 2025 - Juliyanti, Elisa; Haryanto, Sandi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Introduction: Hypertension is one of the health problems that continues to grow every year, the elderly become the age number with a high prevalence due to unbalanced lifestyle and diet behaviors, namely consuming foods with high salt content, lazy movement or exercise, obesity, smoking, and drinking alcoholic beverages. Self-efficacy in hypertensive patients can be improved by motivation and explaining the disease and how to handle it so that someone understands and complies better. Research Objective: The purpose of this study was to determine the relationship between self-efficacy and the incidence of hypertension in the elderly at the Pratama Islam Medina Karawang Clinic in 2025. Research Methods: This type of research is quantitative. Using non-experimental methods with a crosectional approach. The sample was 100 hypertensive respondents with a side nonprobability sampling technique, namely the census with the hypertension self-efficacy questionnaire method and checking blood pressure. Results: The results showed 51 respondents (51.0%) had moderate self-efficacy and 62 respondents (62.0%) with stage 2 hypertension. After doing the chi-square test, the p-value (p,<0.002) was obtained. This shows that there is a significant relationship between self-efficacy and the incidence of hypertension in the elderly at the Pratama Islam Medina Clinic in Karawang in 2025